2018
DOI: 10.3389/fmicb.2018.01865
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Suppression of Innate Antiviral Responses by Hepatitis A Virus

Abstract: Hepatitis A virus (HAV) belongs to the family Picornaviridae. It is the pathogen of acute viral hepatitis caused by fecal-oral transmission. RNA viruses are sensed by pathogen-associated pattern recognition receptors (PRRs) such as Toll-like receptor 3 (TLR3), retinoic acid-inducible gene I (RIG-I), and melanoma differentiation-associated gene 5 (MDA5). PRR activation leads to production of type 1 interferon (IFN-α/β), serving as the first line of defense against viruses. However, HAV has developed various str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Zhu et al found that NDV-induced IL-8 transcript production significantly decreased in cGAS-knockout chicken cells, suggesting that cGAS may also play a role in NDV infection [79]. Asp-Glu-Ala-Asp (DEAD)-box helicase 1 (DDX1) is a member of the DEAD box helicase family and was originally considered to regulate type I IFN and inhibit virus replication [80,81]. Although direct interaction with NDV was not proven, Cheng et al found that Asp-Glu-Ala-Asp (DEAD)-box helicase 1 (DDX1) could strongly bind to poly (I:C) and can inhibit NDV replication via IRF7-mediated IFN activation [82,83].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…Zhu et al found that NDV-induced IL-8 transcript production significantly decreased in cGAS-knockout chicken cells, suggesting that cGAS may also play a role in NDV infection [79]. Asp-Glu-Ala-Asp (DEAD)-box helicase 1 (DDX1) is a member of the DEAD box helicase family and was originally considered to regulate type I IFN and inhibit virus replication [80,81]. Although direct interaction with NDV was not proven, Cheng et al found that Asp-Glu-Ala-Asp (DEAD)-box helicase 1 (DDX1) could strongly bind to poly (I:C) and can inhibit NDV replication via IRF7-mediated IFN activation [82,83].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…This is evidenced by the fact that MAVS, a central protein in IFN pathway signalling, is also targeted at the RNA and protein levels via different mechanisms by FMDV VP1, L pro and 3A [ 44 , 57 , 58 ]. Many other viruses have made MAVS one of the key points in the fight against the antiviral response, including picornaviruses such as HRV-1A, hepatitis A virus (HAV) and SVV, which target MAVS via the 2A and 3C; 2B and precursor 3ABC; and 3C proteins, respectively [ 66 , 67 , 68 ]. Similarly, NEMO, the protein responsible for the formation of the IKK complex, is also impacted by FMDV 3C, responsible for its swine form cleavage, at the Gln383 residue, to prevent NF-kB activation [ 49 , 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the current literature, some picornaviruses seem to focus more on these last two targets rather than on MDA5. This is notably the case of HRV-1A, which targets MAVS via 2A and 3C, hepatitis A virus (HAV), which also targets MAVS via 2B, and precursor 3ABC [ 205 , 206 ]. This is also the case for SVV, which blocks the action of RIG-I via 2C and 3C, a protein also capable of cleaving MAVS and other proteins situated further downstream of the IFN pathway [ 121 , 207 , 208 ].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%